Affinity biosensors using recombinant native membrane proteins displayed on exosomes: application to botulinum neurotoxin B receptor - Desplantes, Richard (Sci Rep, 2017)
The development of simple molecular assays with membrane protein receptors in a native conformation still represents a challenging task. Exosomes are extracellular vesicles which, due to their stability and small size, are suited for analysis in various assay formats. Here, we describe a novel approach to sort recombinant fully native and functional membrane proteins to exosomes using a targeting peptide. Specific binding of high affinity ligands to the potassium channel Kv1.2, the G-protein coupled receptor CXCR4, and the botulinum neurotoxin type B (BoNT/B) receptor, indicated their correct assembly and outside out orientation in exosomes. We then developed, using a label-free optical biosensor, a new method to determine the kinetic constants of BoNT/B holotoxin binding to its receptor synaptotagmin2/GT1b ganglioside (k(on) = 2.3 ×10(5) M(−1).s(−1), k(off) = 1.3 10(−4) s(−1)), yielding an affinity constant (K(D) = 0.6 nM) similar to values determined from native tissue. In addition, the recombinant binding domain of BoNT/B, a potential vector for neuronal delivery, bound quasi-irreversibly to synaptotagmin 2/GT1b exosomes. Engineered exosomes provide thus a novel means to study membrane proteins for biotechnology and clinical applications.